2001
DOI: 10.1023/a:1010409415723
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiaceae, Rickettsia-Like Endosymbionts, and the Origin of Mitochondria

Abstract: Accumulating evolutionary data point to a monophyletic origin of mitochondria from the order Rickettsiales. This large group of obligate intracellular alpha-Proteobacteria includes the family Rickettsiaceae and several rickettsia-like endosymbionts (RLEs). Detailed phylogenetic analysis of small subunit (SSU) rRNA and chaperonin 60 (Cpn60) sequences testify to polyphyly of the Rickettsiales, and consistently indicate a sisterhood of Rickettsiaceae and mitochondria that excludes RLEs. Thus RLEs are considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Actually, rickettsial microorganisms are not necessarily pathogenic species, and are indeed ubiquitous in human populations, where they normally live in peaceful coexistence with the human beings [54]. These organisms represent one of the closest living relatives to bacteria that originated the mitochondria inside most eukaryotic cells [55]. Rickettsiales display small, degraded genomes, with a high propensity of genetic exchange occurring between bacteria that infect the same host and with the eukaryotic hosts themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, rickettsial microorganisms are not necessarily pathogenic species, and are indeed ubiquitous in human populations, where they normally live in peaceful coexistence with the human beings [54]. These organisms represent one of the closest living relatives to bacteria that originated the mitochondria inside most eukaryotic cells [55]. Rickettsiales display small, degraded genomes, with a high propensity of genetic exchange occurring between bacteria that infect the same host and with the eukaryotic hosts themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenomic analyses of mitochondrial proteins place mitochondria in the alphaproteobacterial subdivision, whereas several reconstructions place mitochondria specifically in the Rickettsiaceae family [16-20] or even at the root of the Rickettsiales order [8]. It has also been proposed that Rickettsiae and mitochondria shared a last common ancestor that was probably a parasite of proto-eukaryotic cells [21]. Even though most studies have argued that mitochondria are closely related to the Rickettsiales order, recent studies of the mitochondrion of the green algae Chlamydomonas reinhardtii have proposed that most of the species' mitochondrial protein sister taxa are members of the Rhizobiales and the Rhodobacterales rather than the Rickettsiales order [6].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that the origins of mitochondrial genes are not limited to Rickettsiales and that their creation did not occur in a single event but through multiple successive events. Contrary to what has been believed until now, recent evidence strongly suggests that mitochondria do not have a single common ancestor (Emelyanov, 2001) but likely numerous ancestors, including proto- Rickettsiales , proto- Rhizobiales , proto-alphaproteobacteria and current alphaproteobacterial species. The mosaisism of the mitochondrial genome is also discussed by Esser et al (2007), however, in our study, the use of four different types of mitochondria from four different organisms (protozoa, yeast, louse, human) revealed that the mitochondria of different organisms comprise different elements, while the analysis of the louse multi-chromosomal mitochondrion (Shao et al, 2009) showed that the mitochondria creation model is not fixed: mitochondria do not have a stable or unique form, and thus their evolution cannot be the same.…”
Section: Lateral Inheritancementioning
confidence: 66%